Tradisi Keagamaan Masyarakat Kota Bandung di Bulan Ramadan Tahun 1990-2000 - Muhammad Fajar Nugraha; Sulasman Sulasman; Usman Supendi (UIN Sunan Gunung Djati Bandung, 2018)
In a fairly long period of time in the early 20th century, there were a lot of diverse and unique traditions of the people of Bandung City to discuss. Considering that this material has not been widely discussed in scientific works. Bandung City community tradition during the month of Ramadan takes place so many habits are entrenched in the city of Bandung during the month of Ramadan. The term